2017
DOI: 10.1371/journal.pone.0183165
|View full text |Cite
|
Sign up to set email alerts
|

Dosimetric evaluation of MobiusFX in the RapidArc delivery quality assurance comparing with 3DVH

Abstract: The dosimetric characteristics of MobiusFX, which uses the treatment machine log file to calculate the dose inside the patient body, were analyzed for use in the RapidArc delivery quality assurance (DQA) process. The accuracy and usefulness of MobiusFX in clinical cases was evaluated by comparing the dose calculated by MobiusFX with that calculated by the conventional measurement dose based program, 3DVH. The results of gamma evaluation with three different criteria (3%–3 mm, 4%–3 mm, 5%–3 mm) were analyzed, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 25 publications
(18 reference statements)
0
12
0
Order By: Relevance
“…MobiusFX and 3DVH were not identical, they were generally similar to each other in their verification for 10 prostate, 10 head-and-neck, and 10 chest cancer patients who underwent VMAT. 26 Gamma index evaluation results further demonstrated that independent dose check with Mobius3D and log files based QA with…”
Section: Song Et Al Demonstrated That Although the Dose Reconstructedmentioning
confidence: 86%
See 3 more Smart Citations
“…MobiusFX and 3DVH were not identical, they were generally similar to each other in their verification for 10 prostate, 10 head-and-neck, and 10 chest cancer patients who underwent VMAT. 26 Gamma index evaluation results further demonstrated that independent dose check with Mobius3D and log files based QA with…”
Section: Song Et Al Demonstrated That Although the Dose Reconstructedmentioning
confidence: 86%
“…25 Similarly, Song et al demonstrated that although the dose reconstructed from MobiusFX and 3DVH were not identical, they were generally similar to each other in their verification for 10 prostate, 10 head-and-neck, and 10 chest cancer patients who underwent VMAT. 26 Gamma index evaluation results further demonstrated that inde-…”
Section: B | Independent Dose Checkmentioning
confidence: 87%
See 2 more Smart Citations
“…Mobius3D can calculate a dose distribution for a patient CT dataset directly by using an independent dose calculation algorithm from the primary radiation treatment planning system. Mobius3D has been widely implemented in various institutions and has been applied as a primary-and secondary-checking QA tool to evaluate not only conventional radiotherapy techniques but also advanced ones, such as intensity-modulated radiation therapy (IMRT) and volumetric modulated arc therapy (VMAT) [9][10][11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%